Menavigasi Kedaulatan Digital: Model Diplomasi-Hibrida dalam Manajemen Public Relations di Era Disrupsi Telekomunikasi Satelit - Khairunnisa Nur Alifah; Sintia Rahmatasia; Lovina Hillan Tsaqila; Pramudya Ibnu Subrata (CITACONOMIA, 2026)
The rapid penetration of Starlink’s Low Earth Orbit (LEO) satellite technology in Indonesia has triggered a significant disruption within the national telecommunications landscape, sparking a conflict between global innovation and local protectionism. This conceptual article examines the strategic transformation of Public Relations (PR) from a traditional communication function into a sophisticated instrument of corporate diplomacy. By employing a descriptive qualitative method and grounded in Stakeholder Salience Theory, this study analyzes how global disruptors navigate rigid regulatory environments and economic nationalism. The findings reveal that Starlink’s success is not merely a result of technological superiority but is driven by a